Stat man - Durant, Alan, 1958-; Hudson, Brett (Edinburgh : Barrington Stoke, 2007)
Arnie Kean is a real football boffin. He knows so much about football that his friends call him Stat Man. But what's he like on the pitch? Will he get to play for his team in Saturday's Cup Final?
Keywords: Football -- Fiction